Suppression of Mitochondrial Biogenesis through Toll-Like Receptor 4–Dependent Mitogen-Activated Protein Kinase Kinase/Extracellular Signal-Regulated Kinase Signaling in Endotoxin-Induced Acute Kidney Injury - Smith, Joshua A.; Stallons, L. Jay; Collier, Justin B.; Chavin, Kenneth D.; Schnellmann, Rick G. (The Journal of pharmacology and experimental therapeutics, 2015)
Although disruption of mitochondrial homeostasis and biogenesis (MB) is a widely accepted pathophysiologic feature of sepsis-induced acute kidney injury (AKI), the molecular mechanisms responsible for this phenomenon are unknown. In this study, we examined the signaling pathways responsible for the suppression of MB in a mouse model of lipopolysaccharide (LPS)-induced AKI. Downregulation of peroxisome proliferator-activated receptor γ coactivator-1α (PGC-1α), a master regulator of MB, was noted at the mRNA level at 3 hours and protein level at 18 hours in the renal cortex, and was associated with loss of renal function after LPS treatment. LPS-mediated suppression of PGC-1α led to reduced expression of downstream regulators of MB and electron transport chain proteins along with a reduction in renal cortical mitochondrial DNA content. Mechanistically, Toll-like receptor 4 (TLR4) knockout mice were protected from renal injury and disruption of MB after LPS exposure. Immunoblot analysis revealed activation of tumor progression locus 2/mitogen-activated protein kinase kinase/extracellular signal-regulated kinase (TPL-2/MEK/ERK) signaling in the renal cortex by LPS. Pharmacologic inhibition of MEK/ERK signaling attenuated renal dysfunction and loss of PGC-1α, and was associated with a reduction in proinflammatory cytokine (e.g., tumor necrosis factor-α [TNF-α], interleukin-1β) expression at 3 hours after LPS exposure. Neutralization of TNF-α also blocked PGC-1α suppression, but not renal dysfunction, after LPS-induced AKI. Finally, systemic administration of recombinant tumor necrosis factor-α alone was sufficient to produce AKI and disrupt mitochondrial homeostasis. These findings indicate an important role for the TLR4/MEK/ERK pathway in both LPS-induced renal dysfunction and suppression of MB. TLR4/MEK/ERK/TNF-α signaling may represent a novel therapeutic target to prevent mitochondrial dysfunction and AKI produced by sepsis.